Identity and policies of recognition: discourse and practices in the construction of native peoples' otherness (Quinto Sol, 2013)
In the province of La Pampa (Argentina), when the provincial State seeks to evaluate its policies on cultural diversity, it always retrieves a discourse according to which La Pampa vindicates its indigenous cultura. Such discourse is elaborated and re-elaborated from its central participation in two so-called episodes of  “historical reparation” towards the ranquel people. The policy of historical reparation is analyzed beginning from one of the episodes that took place in the province: the movement of the remains of capitanejo Yancamil from the cementery to the central square of Victorica.The analysis shows the relevance of the State in ethnicity management, and it argues that its policy of recognition –legitimized up to a certain extent by members of the ranquel community-, based upon symbolic recognition, because it avoids historical explanations, hides power relations and inequality, and does not have inmediate legal consequences.
Keywords: Policies of recognition; symbolic recognition; otherness; ranqueles